Changes in zinc and serum proteins due to carbon disulphide exposure. Issue 3 (July 1973) - El-Gazzar, R.; El-Sadik, Yassin M.; Hussein, M.
Abstract : El-Gazzar, R., El-Sadik, Y. M., and Hussein, M. (1973). British Journal of Industrial Medicine, 30, 284-288. Changes in zinc and serum proteins due to carbon disulphide exposure. Serum zinc and proteins have been studied in 82 workers in the Egyptian rayon industry, of whom 40 were at the time exposed to carbon disulphide (CS2 ) and nine had been exposed in the past for a year or more. Thirty-three workers without exposure were used as controls. Carbon disulphide caused depletion of serum zinc by an increase in the rate of zinc excretion and an increase in all serum protein fractions. All these effects are temporary and improve on cessation of exposure.